Trading Go Digital: Experience and Influence of the Digital Phenomenon on Traditional Traders - Zahar, Erlina; Hutabarat, Zuhri Saputra; Afdil, Billy; Muslih, Muhammad; Auliah, Raudatul Jannah; Jannah, Nisma Khoimatul; Putri, Tasya Ayunda; Damayanti, Silphia; Duri, Rafika; Kirom, Najwatul; Alfarizi, Muhammad Taufiq; Sabila, Yiyin; Saputra, Pramana; Alfarizi , Salman; Dairus, Nofrina (International Journal of Multidisciplinary Sciences and Arts, 2024)
The development of digital technology has significantly changed the trade landscape, influencing the way business is conducted around the world. This research aims to investigate the experience and influence of digital phenomena on traditional trade. Qualitative research methods were used, with in-depth interviews and content analysis as the main tools for data collection. Through this approach, a deep understanding of how traditional commerce adapts and evolves in the digital era is gained. The research results show that digitalization has provided challenges and opportunities for traditional trade actors. On the one hand, digitalization has increased market accessibility, enabling traditional traders to reach new customers through online platforms. On the other hand, increasingly powerful digital competitors pose a threat to the continuity of traditional trading businesses. Traditional merchants must adapt quickly to new technology to remain competitive.